RESPONS PERTUMBUHAN SEMAI LIMA KULTIVAR DURIAN ASAL KABUPATEN KAMPAR TERHADAP BERBAGAI PERIODE PENGGENANGAN - Guspa Yuriza; Sujarwati '; Dyah Iriani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Durian (Durio zibethinus Murr.) is a widely cultivated fruit crops in tropical region, especially in Indonesia. The nickname of this plant is King of tropical fruit. Kampar district is one of the largest producers of durian in Riau Province. Geographical location and high rain season of this region cause flooding, therefore Kampar often has periodic flooding. The purpose of this research was to determine the growth response of five cultivars of durian seedling from Kampar in various periods of inundation. Seedlings of five cultivar durian (Malukuik, Terong, Tembaga, Jantung and Kunyit) were given periodic inundation of 5 days and 10 days for 60 days with the same recovery period (5 days with 10 cm inundation height). The results showed that inundation 5 and 10 days significantly reduced all of the durian seedling growth with the observed parameters were the durian seedling height (52% and 70%), number of leaves (64% and 72%), total wet weight (27 % and 22%), root volume (43% and 33%), and root dry weight (45% and 38%). However the ratio of roots shoots increased while the interaction among durian cultivars did not show significant differences.